(3TQM GddeYIs - (3eMeO LhGO Hf eMeO Jbj edG cJGHs
(3ChdgG (B:s
(3bGd GdeUfa QMeg Gddg(B: (3GdJGSY aj GdNjGQ, dG QjH Cf KHhJ GdNjGQ Ydi NdGa GdbGYOI(B...s
(3BNQgG (B:s
(3hbO YQaJ GdQGLM efgeG heKdg ZQje GdejJ eY haGA GdJQcI HGdOjf hbjd eWdbG, hSjLF aj eMdg Ef TGA Gddg(B. (3GdaUd GdYGTQ(B.s
(3JHUQI GdYfhGf (B:s
(3GdeTcGI GdZQhjI aj TQM GddeYI GdOeTbjIs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis